Neutral axis depth and moment redistribution in FRP and steel reinforced concrete continuous beams - Lou, Tiejiong (2014)
The neutral axis depth is considered the best parameter for quantifying the moment redistribution in continuous concrete beams, as exemplified in various design codes worldwide. It is therefore important to well understand the variation of neutral axis depth against moment redistribution. This paper describes a theoretical investigation into the neutral axis depth and moment redistribution in concrete beams reinforced with fibre reinforced polymer (FRP) and steel bars. A finite element model has been developed. The model predictions are in favourable agreement with experimental results. Three types of reinforcement are considered, namely, glass fibre, carbon fibre and steel. Various levels of reinforcement ratio are used for a parametric evaluation. The results indicate that FRP reinforced concrete continuous beams exhibit significantly different response characteristics regarding the moment redistribution and variation of neutral axis depth from those of steel reinforced ones. In addition, it is found that the code recommendations are generally unsafe for calculating the permissible moment redistribution in FRP reinforced concrete beams, but the neglect of redistribution in such beams may be overconservative.